Chinese : an essential grammar - Yip, Po-ching, 1935-; Rimmington, Don (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This new and extended edition of Chinese: An Essential Grammar is an up-to-date and concise reference guide to modern Chinese (Mandarin) grammar. Refreshingly jargon free, it presents an accessible description of the language, focusing on the real patterns of use today. This Grammar aims to serve as a reference source for the learner and user of Chinese, irrespective of level, setting out the complexities of the language in short, readable sections. It is ideal either for independent study or for students in schools, colleges, universities and adult classes of all types. Features include: Three new chapters on speech habits, writing conventions, and new lexicalisation processes Chinese characters, as well as the pinyin romanisation, alongside all examples literal and colloquial translations into English to illustrate language points."--
Originally published: London ; New York : Routledge, 1998, under title: Basic Chinese.
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Chinese language -- Grammar; Chinese language -- Syntax; Chinese language -- Textbooks for foreign speakers -- English; FOREIGN LANGUAGE STUDY / General; LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Journalism